RANCANG BANGUN SENSOR WATER LEVEL K-0135 PADA ALAT SUCTION PUMP - Wardana, Chandra; Sijabat, Salomo; Abdillah, Khairil; Dabukke, Hotromasari (JURNAL MUTIARA ELEKTROMEDIK, 2022)
Suction pump is an electromedical device that is used manually with the help of the user which functions to suck fluids that are not needed by the body. Then the liquid that is not needed is accommodated in a container. Suction is often damaged due to the presence of mucus or liquid that enters the motor rotation. So from the above problems, the author made a Suction Pump Modification equipped with a K-0135 Water Level Sensor. This sensor will also read the liquid that enters the tube with Minimum and Maximum level readings (Low, Middle and Full). The sensor on this tube is very necessary to make it easier for the user to know the liquid is almost full. This research will be conducted in the Sari Mutiara University lab. The type of research method is experimental research, namely conducting direct experiments on the designed tools.The measurement results from the K0135 Water Level Sensor are displayed on the LCD, with measurements of Low, Middle and Full level points.